2017
DOI: 10.3390/nu10010022
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrates for Soccer: A Focus on Skilled Actions and Half-Time Practices

Abstract: Carbohydrate consumption is synonymous with soccer performance due to the established effects on endogenous energy store preservation, and physical capacity maintenance. For performance-enhancement purposes, exogenous energy consumption (in the form of drinks, bars, gels and snacks) is recommended on match-day; specifically, before and during match-play. Akin to the demands of soccer, limited opportunities exist to consume carbohydrates outside of scheduled breaks in competition, such as at half-time. The link… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 57 publications
(100 reference statements)
0
15
0
Order By: Relevance
“…The current study used skill performance that was quite different from these previous studies and more specific to soccer performance. The current study also used a dietary condition (i.e., sports nutrition bars) which is more likely to be used by soccer players before matches when less time is available for food consumption [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current study used skill performance that was quite different from these previous studies and more specific to soccer performance. The current study also used a dietary condition (i.e., sports nutrition bars) which is more likely to be used by soccer players before matches when less time is available for food consumption [5].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, endurance and high-intensity intermittent exercise will be adversely affected by reduced glycogen stores. During soccer matches, this would most likely occur in the second half of a game [3][4][5]. Soccer players with lower levels of muscle glycogen cover less distance and run at lower speeds during the last 15 min of a match [6].…”
Section: Introductionmentioning
confidence: 99%
“…As a general rule of thumb, it is suggested that 30–60 g·h −1 of CHO (glucose polymers e.g., maltodextrin) is consumed during events lasting < 60–150 min [ 78 ], whereas in events > 2.5–3 h, 60–90 g·h −1 (glucose/fructose blends) is the recommended rate [ 7 ]. Whilst beyond the scope of the present review, it is noteworthy that CHO ingestion (in either drink or gel format) during team sport type activity (i.e., <90 min duration) can also improve performance of technical skills (see reference [ 89 ] for an extensive review on this topic), thus providing further evidence for the ergogenic properties of CHO feeding during exercise.…”
Section: Cho and Exercise Performancementioning
confidence: 99%
“…For this reason, research designs based around a regular feeding pattern throughout exercise (i.e., every 15 min) may be limited in their ecological validity. Moreover, when high GI carbohydrates, including those contained within most commercially available sports drinks, are ingested before and during team sport specific exercise, including at half-time, sharp declines in blood glucose concentrations are typically observed during the early stages of the second half [28,29,30,31]. Given the likely mechanisms involved (for a review of this topic, please see [29]), it has been proposed that altering the GI of carbohydrates consumed pre-match and at half-time, may help to counteract these responses in team sports athletes [29].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, when high GI carbohydrates, including those contained within most commercially available sports drinks, are ingested before and during team sport specific exercise, including at half-time, sharp declines in blood glucose concentrations are typically observed during the early stages of the second half [28,29,30,31]. Given the likely mechanisms involved (for a review of this topic, please see [29]), it has been proposed that altering the GI of carbohydrates consumed pre-match and at half-time, may help to counteract these responses in team sports athletes [29]. Theoretically, low GI carbohydrates produce a lower insulinaemic response and a slower delivery of glucose into the systemic circulation, thus helping to maintain blood glucose concentrations throughout the second half [29,31].…”
Section: Introductionmentioning
confidence: 99%